2021
DOI: 10.3390/microorganisms9051109
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Residues Involved in Inhibition of Host Gene Expression by Influenza A/Brevig Mission/1/1918 PA-X

Abstract: The influenza A virus (IAV) PA-X protein is a virulence factor that selectively degrades host mRNAs leading to protein shutoff. This function modulates host inflammation, antiviral responses, cell apoptosis, and pathogenesis. In this work we describe a novel approach based on the use of bacteria and plasmid encoding of the PA-X gene under the control of the bacteriophage T7 promoter to identify amino acid residues important for A/Brevig Mission/1/1918 H1N1 PA-X’s shutoff activity. Using this system, we have id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Importantly, these results demonstrate an evolution in the abilities of NS1 and PA-X proteins to induce host shutoff and show how this is beneficial for IAV. In addition, several in vitro studies have shown that multiple amino acids in PA-X can affect PA-X´s shutoff activity, and that differences between IAV strains or subtypes can occur [ 36 , 38 , 39 , 56 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these results demonstrate an evolution in the abilities of NS1 and PA-X proteins to induce host shutoff and show how this is beneficial for IAV. In addition, several in vitro studies have shown that multiple amino acids in PA-X can affect PA-X´s shutoff activity, and that differences between IAV strains or subtypes can occur [ 36 , 38 , 39 , 56 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NS1 and PA-X genes fused to an N-terminal HA epitope tag were cloned into the pCAGGS HA-NH 2 plasmid [ 38 , 39 ] using SphI and NheI restriction sites. The amino acid sequences were as follows: for PA-X OR , A/Hong Kong/483/1997, H5N1 strain, Pubmed protein ID: AAF74340.1; for PA-X CIR , A/mallard/Italy/3401/2005, H5N1 strain, Pubmed protein ID: AGJ72962.1; for NS1 OR, A/Hong Kong/156/97, H5N1 strain, Pubmed protein ID: O56264.1; and for NS1 CIR, A/duck/Bangladesh/27820/2015, H5N1 strain, Pubmed protein ID: AQY17641.1.…”
Section: Methodsmentioning
confidence: 99%
“…IAV NS1 modulates the inhibition of IFN production through variable interventions ( Baker et al., 2015 ; Cheng et al., 2015 ; Nogales et al., 2017a ; Nogales et al., 2017b ; Nogales et al., 2017c ; Hilimire et al., 2020 ; Martinez-Sobrido et al., 2020 ; Chiem et al., 2022 ; Nogales et al., 2022 ). However, other IAV proteins, including PA-X ( Chiem et al., 2021 ), PB1-F2 ( Varga and Palese, 2011 ; Varga et al., 2012 ), or PB2 have also been shown to be involved in inhibition of host antiviral responses during IAV infection ( Forero et al., 2015 ; Yang et al., 2022 ). Following IAV infection, two major cellular pathways are activated to initiate the antiviral innate immune response: Toll-like receptors (TLRs) and RIG-I-like receptors (RLRs) ( Iwasaki and Pillai, 2014 ) ( Figure 5 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 Inhibition Of Innate Immunitymentioning
confidence: 99%